First‐line treatment in lymphomatoid papulosis: a retrospective multicentre study. (10th October 2017) - Fernández‐de‐Misa, R.; Hernández‐Machín, B.; Servitje, O.; Valentí‐Medina, F.; Maroñas‐Jiménez, L.; Ortiz‐Romero, P. L.; Sánchez Schmidt, J.; Pujol, R. M.; Gallardo, F.; Pau‐Charles, I.; García Muret, M. P.; Pérez Gala, S.; et al.
Summary: Background: Data regarding response to treatment in lymphomatoid papulosis (LyP) are scarce. Aim: To assess the daily clinical practice approach to LyP and the response to first‐line treatments. Methods: This was a retrospective study enrolling 252 patients with LyP. Results: Topical steroids, methotrexate and phototherapy were the most common first‐line treatments, prescribed for 35%, 20% and 14% of the patients, respectively. Complete response (CR) was achieved in 48% of treated patients. Eczematous lesions significantly increased relative risk (RR) of not achieving CR (RR = 1.76; 95% CI 1.16–2.11). Overall median time to CR was 10 months (95% CI 6–13 months), and 78% of complete responders showed cutaneous relapse; both results were similar for all treatment groups ( P  > 0.05). Overall estimated median disease‐free survival (DFS) was 11 months (95% CI 9–13 months) but DFS for patients treated with phototherapy was 23 months (95% CI 10–36 months; P  < 0.03). Having the Type A LyP variant (RR = 2.04; 95% CI 0.96–4.30) and receiving a first‐line treatment other than phototherapy (RR = 5.33; 95% CI 0.84–33.89) were significantly associated with cutaneous early relapse. Of the 252 patients, 31 (13%) had associated mycosis fungoides unrelated to therapeutic approach, type of LyP or T‐cell receptor clonality. Conclusions: Current epidemiological, clinical and pathological data support previous results. Topical steroids, phototherapy and methotrexate are the most frequently prescribed first‐line treatments. Although CR and cutaneous relapse rates do not differ between them, phototherapy achieves a longer DFS. Presence of Type A LyP and use of topical steroid or methotrexate were associated with an increased risk of early relapse.